Analysis of privatization: Different approaches - Tvaronavičiene, Manuela; Kalašinskaite, Kristina (Journal of Business Economics and Management, 2005)
Presented paper strives to elaborate privatization as one of national economy development tools. Performance of privatized enterprises has been taken into consideration. The authors examine different opinions about privatization process and its efficiency taking a close look at the researches that have been already made. Analysis has been targeted to implications’ diversity due to foresee those in transition countries. Governance issues in case of privatization of monopolistic enterprises have been discussed.First Published Online: 14 Oct 2010